The fungicidal effect of sesame essential oil against locally isolated fungi from Al Baha and Baljurash regions - Hamdan Alamri Saleh; Hassan Ali Dosh Mohammed; Bakheet AL-Ghamdi Saleh; Gazi Khaled S.; Fahad Almiman Bandar (BIO Web of Conferences)
Many fungal strains are invading the plants in the agricultural regions and using chemical-based fungicides may cause harm to the plants the then damage the crops. This study aims to assess the fungicidal effect of the composited sesame oil against locally isolated fungi in Al Baha and Baljurash regions in Saudi Arabia. The isolation process focused on infested fields with fungal infection in 11 regions cultivated with olive plants in Al Baha and Baljurash regions, which were then isolated on Potato Dextrose Agar medium for 7 days at 25 C, to be then identified on the genotypic level using ITS genetic marker suitable chromosomal extraction kits and construct the phylogenetic trees by MEGA 11 software. The major 11 fungal pathogens were belonged to Aspergillus niger, Fusarium equiseti, Alternaria tenuissima, Phoma macrostoma, Alternaria alternata, and Aspergillus flavus. While only one nonpathogenic fungal strain was isolated (Trichoderma harzianum). The antifungal activity of the sesame oil in two concentrations was assessed against the isolated fungal strains, the extracted sesame oil with 20 ml concentration showed a promising activity when compared to plain PDA and 10 ml concentration (90.96 to 2.05 mm). In conclusion, sesame oil with maximum concentration can reveal strong fungicidal activity when compared to commercial fungicides and zinc ferrite nanoparticles, therefore, several antifungal approaches must be implemented to combat fungal infections in Al Baha region.